FUNGSI BADAN KEPEGAWAIAN, PENDIDIKAN, DAN PELATIHAN KABUPATEN SUKOHARJO DALAM REKRUITMEN CPNS DITINJAU DARI PRINSIP AKUNTABILITAS DAN TRANSPARANSI - Dewayani, Paramita Putri (Master of Public Administration, Universitas Slamet Riyadi, 2021)
The research purpose was described the function of BKPP of Sukoharjo Regency in civil servant recruitment viewed from the principles of accountability and transparency. The research used descriptive qualitative method. Data collection techniques were used interviews, observation, and documentation. The data analysis technique was used Miles and Huberman’s intractive model. Validity data testing was used triangulation techniques. The evaluation of BKPP of Sukoharjo Regency function in the implementation of CPNS recruitment is viewed from the principles of accountability and transparency conveyed by Sedarmayanti (2013). The results of the study indicated that 1 ) Function of BKPP Sukoharjo regency in civil servant recruitment in terms of the accountability principle appears from the implementation of civil servant recruitment carried out in accordance with the legislation in force as well as the recruitment of civil servant accountable to the public and made a report to the parties concerned. 2 ) Functions of the BKPP of Sukoharjo Regency in terms of the transparency principle, the recruitment of CPNS is to carry out the recruitment of CPNS openly step by step. The announcement, application and filtering system is implemented transparently through the application of information technology so that the public can access it easily. Based on the research results, it can be concluded that the BKPP Sukoharjo Regency has implemented the principles of accountability and transparency in carrying out its functions in the implementation of CPNS recruitment in Sukoharjo Regency.